Doctors Are Aggrieved—Should They Be? Gross Negligence Manslaughter and the Culpable Doctor. (August 2020) - Robson, Michelle; Maskill, Jon; Brookbanks, Warren
Doctors may also be criminals. Mercifully, this is a rare event but no health professional is infallible, mistakes happen and the challenge is to distinguish inadvertence from wilful disregard for the consequences. Healthcare professionals are uneasy about the readiness of the current law to attribute criminal responsibility accompanied by a failure to recognise the highly pressurised context in which sub-standard practice occurs. This article argues that the offence of gross negligence manslaughter is improperly defined and fails to target those doctors whom society should criminalise. Alternatives to gross negligence manslaughter to include culpable homicide adopted in Scotland and the major departure test favoured by New Zealand are considered before advocating a more radical approach—the sliding scale of negligence. Using existing tests in civil and administrative law, a more objective test of gross negligence is proposed, with culpability as a mandatory requirement for a doctor to be convicted of a crime. It is contended the law must move away from the stance a patient's death is required for medical negligence to become a crime, an outcome bias, to a conduct biased offence. There is no underlying reason why culpable gross negligence causing serious harm should not also be subject to criminal sanction. The recent sentencing guidelines demonstrate the law is sophisticated enough to distinguish reprehensible conduct from careless behaviour. It is now time for the legal test to also acknowledge all the circumstances of the alleged crime.